Assessing The Impact of Transglutaminase and Methylcellulose on Physical Properties of Seitan-Infused Plant-based Meat Analog Patties Compared to Beef Patties - Mohd Radzi , Nur Raudhatul Syahindah; Zulkifli, Noroul Asyikeen; Ismail, Ishamri; Huda, Nurul (Indonesian Food Science and Technology Journal, 2025)
This study seeks to develop plant-based patties (PBP) by varying TVP-to-seitan ratios (30:70, 50:50, and 70:30) and adjusting methylcellulose (MC) and transglutaminase (TG) concentrations (MC: 2%, TG: 2%, and MC+TG: 1+1%). These formulations were compared to a beef patty (control, CON) across several parameters including appearance, cooking loss, color, texture, and surface area. While PBP exhibited similar appearances, they differed from beef patties in terms of shrinkage. PBP was firmer (0.31-3.18 N) with higher seitan content but less tough than CON (13.77 N). Additionally, PBP showed larger surface areas than CON, and the addition of TG reduced shrinkage and cooking loss, particularly with higher seitan content. Although all PBP appeared darker (lower L* values) than CON, the redness (a*) and yellowness (b*) remained unaffected by the base ingredients and binders. Optimal PBP formulations, containing 70% seitan and either 2% TG or a combination of 1% MC and 1% TG, achieved a balance between texture, reduced shrinkage, and cooking loss but did not perfectly match the color of conventional patties.